Student perspectives on the use of a Java library for novices - Barros, João Paulo (2019)
This experience report presents and discusses students’ perspectives about the use of a library specifically built for introductory programming courses using the Java programming language. It was motivated by sporadic criticism by some students regarding the use of ”non-professional” tools. All the inquired students had already attended an introductory computer pro- gramming course (CS1) where the library was used. We used a student-focused approach, based on an anonymous questionnaire and semi-structured interviews, to obtain information about the students’ opinions and perceptions related to the use of the library. In order to avoid contamination regarding the opinion about ”non-professional” tools, students were also asked about the use of BlueJ IDE. The interviews were conducted after the follow-up programming course, where a professional IDE was used, thus allowing students to express a more informed opinion on the relative merits, for novices, of each IDE. Our results clearly point to a large positive opinion about the use of the BlueJ environment, but less so about the library. Most students do not like the use of graphics as they lack the needed mathematical background, namely Cartesian geometry and simple trigonometry, but would approve the use of the library in part of the semester without the geometry component.